5-3(5x-6)+2x=

Simple and best practice solution for 5-3(5x-6)+2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(5x-6)+2x= equation:


Simplifying
5 + -3(5x + -6) + 2x = 0

Reorder the terms:
5 + -3(-6 + 5x) + 2x = 0
5 + (-6 * -3 + 5x * -3) + 2x = 0
5 + (18 + -15x) + 2x = 0

Combine like terms: 5 + 18 = 23
23 + -15x + 2x = 0

Combine like terms: -15x + 2x = -13x
23 + -13x = 0

Solving
23 + -13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -13x = 0 + -23

Combine like terms: 23 + -23 = 0
0 + -13x = 0 + -23
-13x = 0 + -23

Combine like terms: 0 + -23 = -23
-13x = -23

Divide each side by '-13'.
x = 1.769230769

Simplifying
x = 1.769230769

See similar equations:

| 5x-7=9(x-3) | | -18+x^2+-3x=0 | | n=21.26-0.8b | | h(t)=-16t^2+17t+136 | | 4/15-3/20= | | 3/4=20× | | 12x^2+48x-144=0 | | .5(x+12)=-2 | | 1/8x^2-5/6x=7/12 | | (x/(2sqrtx^2-2500))-1/5=0 | | 8=9x+-7 | | 33÷4/3 | | y+3z=15 | | 11/-3 | | (x/2sqrtx^2-2500)-1/5=0 | | 6x+6.44=4x+10 | | 5a^2X/8ax^2 | | 3x+2y-z+w=-5 | | 1/9-1/27 | | 50x=40x+100 | | 4s+2(4s+1)=125 | | -8d-5d+7d=32 | | 3(x)+(x+25)+x=435 | | S^3-S=0 | | 90x-10x^2=180 | | 2(4+8)=128 | | 2(x+6)+(3x-27)=180 | | 54=18m | | 4q-66= | | .05x+x=8505 | | 9sin^2x-5=0 | | 12t-8t=-32 |

Equations solver categories